Importancia de los microbiomas del suelo en la producción agrícola sostenible de solanáceas - García Villacres, Ivonne Nuria (2023)
The soil is the main factor of all agricultural activity for sustainable agriculture, in this way the soil microbiome has the purpose of preserving natural resources, improving environmental quality with a reduction of possible environmental contaminants and in this way maximizing agricultural quality. Therefore, a microbiome is a great variety of microorganisms formed by diversities of thousands and millions of fungi, bacteria, actinomycetes and protozoa. The soil microbiome refers to the set of microorganisms that are found in this ecosystem and that are part of vital processes. related to their environment such as the growth of plants, the cycle of carbon and other nutrients. The objective of this study was to establish the Importance of soil microbiomes in the sustainable agricultural production of Solanaceae. So, to carry out the research, the exhaustive compilation of information processed through analysis, synthesis, and summary techniques of various bibliographic sources available on different digital platforms was promoted. The determination of soil microbiomes involves a combination of molecular, genetic, and microscopic techniques that allow the diversity and function of microbial communities to be characterized. It was detected that through the deliberate inoculation of the soil microbiome in the Solanaceae family it comprises a promising tool to manage an agent that allows crop protection and nutrient supply. In this way, it is concluded that the identification of soil microbiomes today is an important tool to improve the production of solanaceous crops since it allows increasing the potential of the soil-plant consortium.